Implementing non-formal education for the locals: the case of Tanah Ombak and fishermen community - Febriany, Sarah (Institute for Advanced Science, Social, and Sustainable Future, 2023)
This study is a program evaluation research conducted in Non-Formal Education by the Tanah Ombak Community. This community is here to change the next generation of Purus (coastal area) to be better, cut off from the poverty chain that has been entangled and free from a marginalized environment. Tanah Ombak non-formal education is a public space for activities in the arts and literacy for school-age children and adolescents in Purus. The goal is for them to leave the